2020
DOI: 10.21203/rs.3.rs-67821/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catastrophic Health Expenditures for Children with Disabilities in Iran: A National Survey

Abstract: Background: Higher health costs and financial burden are imposed on people with disabilities due to their health status associated with their disability. Measuring the incidence of catastrophic health expenditures (CHE) can provide good evidence for health policymakers to assess the current state of financial protection of the health system. The aim of this study was to investigate the percentage of households with disabled children aged 0 to 8 years who had faced CHE due to the health costs of these children … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…33 According to findings of various studies in Iran, the variables of using inpatient, outpatient, and dental services, low education, rural life and low economic status of the household, being a female head of the household, not having insurance, having a child under 5 years, having an elderly person and a person with a disability in the household are the factors that determine CHE in Iran. 30,34 According to our study, having supplementary insurance did not lead to greater financial protection and nor reduced the odds of facing CHE. This finding contradicts the findings of many previous studies.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…33 According to findings of various studies in Iran, the variables of using inpatient, outpatient, and dental services, low education, rural life and low economic status of the household, being a female head of the household, not having insurance, having a child under 5 years, having an elderly person and a person with a disability in the household are the factors that determine CHE in Iran. 30,34 According to our study, having supplementary insurance did not lead to greater financial protection and nor reduced the odds of facing CHE. This finding contradicts the findings of many previous studies.…”
Section: Discussionmentioning
confidence: 55%
“…Based on the results of the preceding study, the expansion of prepayment mechanisms, integration of insurance funds and designing insurance service packages to cover chronic diseases have been proposed as appropriate solutions for financial protection against CHE 33 . According to findings of various studies in Iran, the variables of using inpatient, outpatient, and dental services, low education, rural life and low economic status of the household, being a female head of the household, not having insurance, having a child under 5 years, having an elderly person and a person with a disability in the household are the factors that determine CHE in Iran 30,34 …”
Section: Discussionmentioning
confidence: 99%
“…The total, urban, and rural CHE incidence all showed a variable trend, ranging from 0.3 to 32.7% for total households. The lowest percentage of CHE in the studies conducted from 2000 to 2020 at the national population level is reported by Hajizadeh M et al in 2003 among 3514 Iranian households using hospital services(0.3%) ( 23 ), while the highest percentage of CHE rate is reported by Moradi, G et al in 2020 among 2000 Iranian households with disabled children aged 0 to 8 years (32.7.3%) ( 24 ). Further analysis reveals that the percentage of CHE is 3.83% in studies that use primary data (N:13) and 3.37% in studies that use secondary data (N:42).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with primary data use the questionnaires and interviews for data collection, while those with secondary data use data from the Household Income and Expenditure Survey (HIES) which is collected regularly by the Iran Statistics Center (ISC). Among reviewed studies, three studies conducted at the national level have declared higher CHE percentages (15.31% in 2001 ( 25 ), 11.58% in 2013 ( 23 ), and 32.7% in 2020 ( 24 )) which have increased the overall mean of CHE from 2.48% to 3.19 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation